Separation in clusters of rural properties regarding good agricultural practices in the cultivation of coffee - Pereira, Sérgio Parreiras; Guimarães, Rubens José; Rosa, Beatriz Terezinha; Antonialli, Luiz Marcelo; Romaniello, Marcelo Marcio (Coffee Science - ISSN 1984-3909, 2014)
The increase in the demand for sustainable coffee, certified in the global market, and in order for Brazil to maintain provision leadership, is notorious and necessary for the implementation of public politics in order to insert new coffee producers in this differentiated coffee market. The separation into clusters, statistical technique of the applied social sciences, emerges as a strategy to separate coffee producer groups according to good agricultural practices. The objective of this work was to evaluate the separation by cluster methodology considering the performance of groups of rural properties in relation to good agricultural practices in coffee cultivation, aiming at identifying differentiated technical assistance and rural extension policies. The object of the study was the Associação dos Agricultores Familiares de Santo Antônio do Amparo (AFASA). The research was conducted with 32 coffee producers between the months of May and June of 2009, through a survey type structured questionnaire. The statistical analyses were performed by the SPSS statistical softwear, which separated the coffee producers into two groups, with Group 1 formed by 17 producers and Group 2 by 15 producers. The discriminant analysis allowed us to identify the variables which most discriminated one group from the other. We conclude that the producers inserted into Group 1 presented better performance regarding the good agricultural practices when compared to Group 2. The proposal methodology was capable of categorizing groups of coffee producing properties according to performance regarding good agricultural practices.